Circular linkages between soil biodiversity, fertility and plant productivity are limited to topsoil at the continental scale. Issue 3 (13th June 2017) - Delgado‐Baquerizo, Manuel; Powell, Jeff R.; Hamonts, Kelly; Reith, Frank; Mele, Pauline; Brown, Mark V.; Dennis, Paul G.; Ferrari, Belinda C.; Fitzgerald, Anna; Young, Andrew; Singh, Brajesh K.; Bissett, Andrew
Summary: The current theoretical framework suggests that tripartite positive feedback relationships between soil biodiversity, fertility and plant productivity are universal. However, empirical evidence for these relationships at the continental scale and across different soil depths is lacking. We investigate the continental‐scale relationships between the diversity of microbial and invertebrate‐based soil food webs, fertility and above‐ground plant productivity at 289 sites and two soil depths, that is 0–10 and 20–30 cm, across Australia. Soil biodiversity, fertility and plant productivity are strongly positively related in surface soils. Conversely, in the deeper soil layer, the relationships between soil biodiversity, fertility and plant productivity weaken considerably, probably as a result of a reduction in biodiversity and fertility with depth. Further modeling suggested that strong positive associations among soil biodiversity–fertility and fertility–plant productivity are limited to the upper soil layer (0–10 cm), after accounting for key factors, such as distance from the equator, altitude, climate and physicochemical soil properties. These findings highlight the importance of surface soil biodiversity for soil fertility, and suggest that any loss of surface soil could potentially break the links between soil biodiversity–fertility and/or fertility–plant productivity, which can negatively impact nutrient cycling and food production, upon which future generations depend.